2006
DOI: 10.1002/pmic.200500400
|View full text |Cite
|
Sign up to set email alerts
|

Identification of target proteins of N‐acetylglucosaminyl transferase V in human colon cancer and implications of protein tyrosine phosphatase kappa in enhanced cancer cell migration

Abstract: To gain a better understanding of the mechanism underlying colon cancer and to search for potential markers of colon cancer prognosis, a comparative proteomic analysis of colon cancer WiDr cells was conducted using 2-DE and lectin blot, followed by identification based on ESI-MS. Through these approaches 14 proteins were identified as candidate target proteins for N-acetylglucosaminyl transferase V (GnT-V) that would be expected to be implicated in the progression of colon cancer. We selected protein tyrosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 15 publications
3
39
0
Order By: Relevance
“…23,24 It has also been suggested in a recent study that cleavage of PTPRK protein is implicated in colon cancer metastasis. 25 Here we show that EBV infection of HL cells down-regulates PTPRK expression and that this leads to their increased growth and survival. We observed these effects not only in KM-H2 cells that were artificially infected with a recombinant EBV but also following the loss of the EBV genome from L591 cells that are presumed to derive from EBV-positive primary HRS cells.…”
Section: Discussionmentioning
confidence: 66%
“…23,24 It has also been suggested in a recent study that cleavage of PTPRK protein is implicated in colon cancer metastasis. 25 Here we show that EBV infection of HL cells down-regulates PTPRK expression and that this leads to their increased growth and survival. We observed these effects not only in KM-H2 cells that were artificially infected with a recombinant EBV but also following the loss of the EBV genome from L591 cells that are presumed to derive from EBV-positive primary HRS cells.…”
Section: Discussionmentioning
confidence: 66%
“…60 Loss of RPTP phosphatase activity from the plasma membrane would likely result in increased β-catenin tyrosine phosphorylation, thus promoting cellular migration. This is supported by studies of PTPκ cleavage, in which PTPκ cleavage has been associated with increased cell migration 61 and translocation of the PTPκ-ICD into the nucleus results in increased β-catenin-regulated transcription. 24 Likewise, cadherin cleavage would promote the translocation of β-catenin from the plasma membrane to the cytosol, as has been demonstrated in the case of N-cadherin cleavage.…”
supporting
confidence: 58%
“…1A). We have identified target proteins for GnT-V from secreted glycoproteins that bind to lens culinaris column (13). However, glycoproteins did not necessarily bind to the lectin column, which prompted us to search for target proteins in this study from total secretome of WiDr:mock cells that expresses GnT-V at very low, almost negligible levels and GnT-V overexpressing cells (WiDr:GnT-V) (Fig.…”
Section: Timp-1 Is a Target Protein For Gnt-v In Colon Cancermentioning
confidence: 99%
“…For this, we adopted proteomics and glycomics techniques in which two-dimensional electrophoresis, lectin blot analysis, and MS-based protein identification were linked. We have previously reported that these approaches allowed us to identify several candidate proteins that are assumed to be involved in progressions of gastric cancer (12) and colon cancer (13) and have validated these approaches for discovery of biomarker by showing the role of aberrant glycosylation of protein tyrosine phosphatase as an example in cancer cell migration (13). In this article, we report that additional candidate proteins were identified including tissue inhibitor of metalloproteinase-1 (TIMP-1) as the target for GnT-V and, more importantly, that the aberrant glycosylation of TIMP-1 is closely correlated with invasive/metastatic potential of colon cancer cell WiDr.…”
mentioning
confidence: 99%